Correlation analysis of inflammatory chemokine CXCL8 and lymphoid axillary lymph node metastasis in breast cancer - Li, Ceng; Hou, Jinxiang (Journal of Medical Biochemistry, 2025)
Background: In this study, we analyzed the relationship between serumchemokine CXC ligand 8 (CXCL8) and breast cancer (BC) and the predictive effect on axillary lymph node metastasis.Methods: 121 BC patients and 104 healthy controls were included, and serum CXCL8 was detected by ELISA to compare the differences in the levels of CXCL8 and tumor markers in the two study groups. Pathological examinations revealed that 36 of the patients had axillary lymph node metastasis. To further evaluate the diagnostic value, the ROC curve was employed to analyze the ability of CXCL8, tumor marker and combined color Doppler ultrasound blood flow richness grade (Adler grade) to assess axillary lymph node metastasis in BC patients.Results: Serum CXCL8 CEA, CA153, and CA27.29 were higher in BC patients than in controls (P < 0.05). Patients with lymph node metastasis had higher levels of CXCL8 CEA, CA153, and CA27.29 (P < 0.05). The AUC of CXCL8+tumor markers+Adler grade for the diagnosis of lymph node metastasis was 0.903 (95% CI: 0.850-0.957), with a sensitivity of 86.11% and a specificity of 82.35% (P < 0.001).Conclusion: High expression of CXCL8 is closely associated with BC lymph node metastasis.
Keywords: Breast cancer; Lymphatic node transfer; CXCL8; Tumor marker